Adsorption of cellulase on cereal brans: a simple functional model from response surface methodology - Chigurupati S. Rao; Rui Sergio F. da Silva (Semina: Ciências Sociais e Humanas, 2010)
A functional model based on Langmuirian adsorption as a limiting mechanism was proposed to explain the effect of cellulase during the enzymatic pretreatment of bran, conducted prior to extraction of proteins, by wet alkaline process from wheat and buckwheat bran materials. The proposed model provides a good fit (r = 0.99) for the data generated thru predictive model taken from the response surface methodology, permitting calculation of a affinity constant (b) and capacity constant (k), for wheat bran (b = 0.255 g/IU and k = 17.42%) and buckwheat bran (b = 0.066g/IUand k = 78.74%).